2004
DOI: 10.1037/1064-1297.12.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Stimulus, Reinforcing, Physical Dependence, and Antinociceptive Effects of Oxycodone in Mice, Rats, and Rhesus Monkeys.

Abstract: Despite oxycodone's (4,5-epoxy-14-hydroxy-3-methoxy-17-methylmorphinan-6-one) history of clinical use and the attention it has received as a drug of abuse, few reports have documented its pharmacology's relevance to its abuse or its mechanism of action. The purposes of the present study were to further characterize the analgesic effects of oxycodone, its mechanism of action, and its effects in terms of its relevance to its abuse liability. The results indicate that oxycodone had potent antinociceptive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 30 publications
8
57
0
Order By: Relevance
“…In particular, there have been relatively few preclinical reports characterizing the reinforcing and dependence-producing properties of the drug. In terms of its reinforcing-related effects, oxycodone has been reported to be self-administered by laboratory animals, including rats (Beardsley et al, 2004) and mice (Zhang et al, 2009(Zhang et al, , 2015. Oxycodone also produces conditioned place preference in rats (Rutten et al, 2011) and mice Kirkpatrick and Bryant, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, there have been relatively few preclinical reports characterizing the reinforcing and dependence-producing properties of the drug. In terms of its reinforcing-related effects, oxycodone has been reported to be self-administered by laboratory animals, including rats (Beardsley et al, 2004) and mice (Zhang et al, 2009(Zhang et al, , 2015. Oxycodone also produces conditioned place preference in rats (Rutten et al, 2011) and mice Kirkpatrick and Bryant, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that they did not analyze the somatic signs of oxycodone withdrawal because of the "severity of … withdrawal" it produced (Hutchinson et al, 2009). Beardsley et al (2004) reported that oxycodone dose-dependently suppressed signs of spontaneous withdrawal in morphine-dependent monkeys and concluded that oxycodone shared cross-dependence with morphine. Also pertinent to the abuse-related effects of oxycodone is its ability to induce locomotor sensitization and its discriminative stimulus effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, few studies in laboratory animals (Beardsley et al, 2004;Woods et al, 2002) and no studies in humans have been conducted to examine systematically the reinforcing effects of some of the most commonly abused prescription opioids, such as oxycodone. Fentanyl abuse has also increased substantially in the last decade, and although the reinforcing effects of fentanyl have been examined in some detail in laboratory animals (eg Ko et al, 2002;Morgan et al, 2002), few studies have examined its reinforcing effects in humans (Zacny et al, 1996b) and no studies have characterized its reinforcing effects in opioid abusers.…”
Section: Introductionmentioning
confidence: 99%
“…Oxycodone has been thought to exert its pharmacological activity through activation of -opioid receptors (Nielsen et al, 2000); however, other studies suggested that the analgesic and abuse effects of oxycodone are probably mediated through -opioid receptors (Beardsley et al, 2004;Nozaki and Kamei, 2007). Oxycodone is the most often prescribed opioid agonist in the United States (Hays, 2004).…”
mentioning
confidence: 99%